Primary perianal extramammary Paget's disease: Case report with review - Anshuman Pandey; Pradyuman Singh; Rajkumar Mishra; Alankar Gupta (Wolters Kluwer Medknow Publications, 2016)
Extramammary Paget's disease (EMPD) is a rare cancer which involves the skin and apocrine glands. It involves the vulva, perianal region, scrotum, penis and axilla. Primary disease originates from intraepidermal cells and secondary originates from underlying neoplasm. The disease presents with thickened plaque like lesion with erythema or white scaly appearance. The cancers of urinary tract like the bladder, urethra and prostrate are associated with EPMD involving the genitalia and rectal tumours are associated with perianal disease. The disease affects females more than males with the median age being 72 years. Primary perianal EMPD is even rare in presentation. It is a slow growing tumour and the prognosis is usually favourable other than advanced stage and old age. The surgical resection with clear margins is considered to be the standard of care and provides good outcomes. However, if surgery is not feasible other treatment options like imiquimod 5% topical cream and radiation therapy may be offered. We present a young male with perianal EMPD who was managed with surgical resection with clear margins with split skin graft leading to a favourable outcome.